Evaluasi Peran Otoritas Jasa Keuangan dalam Pengawasan Implementasi Standar Audit 701 (2021) - Novita, Shinta; Fatima, Eliza (Owner : Riset dan Jurnal Akuntansi, 2024)
The objectives of this study are to provide an overview of the benefits of communicating key audit matters (KAM) for OJK's oversight function, to identify findings related to KAM in United Kingdom and Malaysia, and how those regulators have responded to those findings, and to evaluate OJK's response related to KAM. This research is carried out by in-depth interviews with supervisors and analysts from the Directorate of Regulation and Development of the OJK Capital Market Sector. KAM communication provided benefits in OJK's supervisory function, among others, in determining the items to be reviewed in the Issuer's financial statements and in reviewing the audit responses stated in the auditor's report have been supported by the auditor's working papers. In carrying out their oversight function, the United Kingdom and Malaysia found, among others, that the average number of KAM and words in communicating KAM in the auditor's report continued to decline, the content of KAM of companies audited by Big 4 audit firms had more words for the same number of KAM, and the benefits of communicating KAM decreased because KAM disclosures were boilerplate. OJK's response in relation to the implementation of SA 701 (2021) is to draft OJK regulations related to KAM and to prepare a study related to the first-year implementation of SA 701 (2021). Based on these responses, it is reflected that OJK has an important role in the implementation support stage to ensure that the policy implementation runs well in the long term.